Proteomic Analysis of Pollen and Blossom Honey from Rape Seed Brassica Napus L - Borutinskaitė, Veronika; Treigytė, Gražina; Matuzevičius, Dalius; Zaikova, Ilona; Čeksterytė, Violeta; Navakauskas, Dalius; Kurtinaitienė, Bogumila; Navakauskienė, Rūta (Journal of Apicultural Science, 2017)
In the study, honey from oilseed rape Brassica napus L., and both hand-collected (winter rape Visby and Cult) and bee-collected pollen of oilseed rape were analyzed for their proteome content, in order to see if any plant proteins were present to allow the proteo-typing of the oilseed rape honey. Proteins were fractionated by two-dimensional gel electrophoresis (2DE), stained by Coomassie blue and then analyzed by mass spectrometry. All identified proteins were divided into few groups due to their biological function. In 2DE gels with separated proteins from blossom honey, only bee (Apis mellifera) main proteins (Major royal jelly protein 1-5 and Glucosidase) were found. So we analyzed all proteins using gel-free based analysis with the SYNAPT G2 high definition mass spectrometry. We identified proteins that were present in both oilseed rape pollen and honey (Bna, Polygalacturonase, Non-specific lipid-transfer protein, GAPDH and others). We believe that these proteins are important for the nutritional value of plant pollen-enriched honey and further research is required on honey and honeybee pollen protein.